Digitalisasi Sastra Jawa Digitalisasi Sastra Jawa: Implementasi Media Blog untuk Meningkatkan Keterampilan Menulis Cerkak - Dyah Kurniawati Dyah Kurniawati; Darni; Octo Dendy Andriyanto (Universitas Veteran Bangun Nusantara Sukoharjo, 2026)
This study aims to describe the improvement of students’ cerkak (Javanese short story) writing skills and digital literacy through the use of blogs in madrasah enviroment. The research is motivated by low interest in Javanese literature and creative obstacles found in conventional methods. Initial data from 18 students at MTsN Kota Madiun showed sub-optimal results, with only 2 students achieving the